Pan Kosicki Framing Analysis about Sexual Harassment in Riau University on Kompas.com and Tribunnews.com - Syavira Aulia (SEMIOTIKA: Jurnal Komunikasi, 2022)
A sexual harassment case occurred at the University of Riau, it is suspected that one of the students of International Relations at the University of Riau was sexually harassed by her thesis advisor. This sexual harassment case was denied by the alleged perpetrator Dean of FISIP Riau University Syafri Harto. This has attracted the attention of many Indonesian media to highlight the issue of sexual harassment that occurred at the University of Riau including kompas.com and tribunnews.com. This study aims to describe how the media tribunnews.com and kompas.com in framing cases of sexual harassment that occurred at University of Riau. The method used in this research is quantitative methods with constructivism paradigm. The theory used in this study is framing theory by Zhongdang Pan and Gerald M. Kosicki, in this theory the structure of the news to be analyzed is the syntactic structure, script structure, thematic structure, and rhetorical structure. The results show that the two media frame this case in the different way. Tribunnews.com further highlights the chronology of events quoted from the @komahi_ur instagram account. Kompas.com emphasizes the alleged rebuttal of the Dean of FISIP Syafri Harto for the sexual harassment case that carried his name.Keywords: framing, pan kosicki, sexual harassment, universitas riauKata kunci: framing, pan kosicki, pelecehan seksual, universitas riau.